Can the Future of ID Escape the Inertial Dogma of Its Past? The Exemplars of Shorter Is Better and Oral Is the New IV. (29th December 2022) - Davar, Kusha; Clark, Devin; Centor, Robert M; Dominguez, Fernando; Ghanem, Bassam; Lee, Rachael; Lee, Todd C; McDonald, Emily G; Phillips, Matthew C; Sendi, Parham; Spellberg, Brad
Abstract: Like all fields of medicine, Infectious Diseases is rife with dogma that underpins much clinical practice. In this study, we discuss 2 specific examples of historical practice that have been overturned recently by numerous prospective studies: traditional durations of antimicrobial therapy and the necessity of intravenous (IV)-only therapy for specific infectious syndromes. These dogmas are based on uncontrolled case series from >50 years ago, amplified by the opinions of eminent experts. In contrast, more than 120 modern, randomized controlled trials have established that shorter durations of therapy are equally effective for many infections. Furthermore, 21 concordant randomized controlled trials have demonstrated that oral antibiotic therapy is at least as effective as IV-only therapy for osteomyelitis, bacteremia, and endocarditis. Nevertheless, practitioners in many clinical settings remain refractory to adopting these changes. It is time for Infectious Diseases to move beyond its history of eminent opinion-based medicine and truly into the era of evidenced-based medicine. Abstract : Infectious Diseases practitioners in many clinical settings may remain refractory to changing practice from historical precedence, despite multiple, modern, randomized controlled trials. We must move beyond our history of eminent opinion-based medicine and truly into the era of evidenced-based medicine.